Fatty acid and amino acid profiles in muscle longissimus lumborum et thoracis of the indigenous Prestice Black-Pied pig breed in comparison with a commercial pig hybrid - Pavel Nevrkla; Eva Weisbauerová; Pavel Horký; Zdeněk Hadaš; Miroslav Rozkot; Drahomíra Čtvrtlíková Knitlová (Italian Journal of Animal Science)
The objective of the study was to analyse the fatty acid profile (FA) and amino acid profile (AA) in the musculus longissimus lumborum et thoracis (MLLT) in two contrast pig populations. The study was carried out on a total of 39 pigs (19 barrows and 20 gilts) of the indigenous Prestice Black-Pied Pig (PB) and 37 pigs (17 barrows and 20 gilts) of the three-breed commercial hybrid of Large White × Landrace × Large Whitesireline (CH). The pigs were kept in the same conditions of diet and management. The slaughter was carried out at the average weight of 95 kg. Sex of the evaluated pigs was also taken into account. The CH pigs showed lower contents of saturated FA (p < 0.01), monounsaturated FA (MUFA; p < 0.05) and a higher content of n-6 polyunsaturated FA (PUFA; p < 0.05), more favourable health indexes, expressed as lower values of atherogenic (p < 0.001), thrombogenic (p < 0.001) and saturation (saturated/unsaturated FA) index (p < 0.001) and positively higher values of hypocholesterolemic/hypercholesterolemic FA ratio (p < 0.01). The gilts showed lower content of MUFA (p < 0.05). Significant (p < 0.05) interaction effects between genotype and sex were recorded for the caprylic acid, capric acid, lauric acid, tridecylic acid, myristic acid, stearic acid, arachidic acid, α-linolenic and γ-linolenic acid (p < 0.01), with the highest content found in PB barrows. Differences in the AA profiles in the MLLT muscle were only minimal. The PB pigs showed higher proportion (p < 0.05) of threonine, isoleucine and aspartic acid. Higher proportions of threonine and valine were observed in barrows (p < 0.05). The results indicate that the evaluated populations of pigs are characterised by significantly different composition of FA. The health indexes suggest more favourable values in the meat of CH pigs.